European Efficiency or Inefficiency in Economic Growth Through Digital Transformation - Mircea Radu Georgescu; Anca Elena Lungu; Ioana Andreea Bogoslov; Eduard Alexandru Stoica (Scientific Annals of Economics and Business, 2023)
The current global changes bring to the fore the importance of the innovation and digital transformation for economic development. Under the previous assumption, an objective evaluation of the economic growth discrepancies, considering the digitalization process, is required. The main goal of the present research is to analyse the economic growth of the European countries, based to the digitalization process, by using an input-output method. Under these circumstances, a Data Envelopment Analysis (DEA) was performed, considering the digitalization dimensions of DESI Index as input and the economic growth (annual %) as output. Based on the proposed model, the results highlighted the bidirectional relationship between economic growth and digitalization. Consistent with the research results, the European countries can be divided in two main categories: the efficient and the inefficient. On one hand, we can find the relatively efficient European states in terms of achieving the economic growth through digitalization (Ireland, Romania, Croatia and Greece). On the other hand, there is a numerous list of the inefficient ones, including important countries like Finland, Germany or France. Obviously, a remarkable aspect related to their situation is that, considering the national available inputs, an output maximization will be possible. According to the proposed model, the efficient countries can serve as peers or optimal benchmarks for solving the issue of relative inefficiency, by adapting and implementing their good practices.